2015
DOI: 10.1111/adb.12316
|View full text |Cite
|
Sign up to set email alerts
|

Pulling habits out of rats: adenosine 2A receptor antagonism in dorsomedial striatum rescues meth‐amphetamine‐induced deficits in goal‐directed action

Abstract: Addiction is characterised by a persistent loss of behavioural control resulting in insensitivity to negative feedback and abnormal decision-making. Here we investigated the influence of methamphetamine (METH)-paired contextual cues on decision-making in rats. Choice between goal-directed actions was sensitive to outcome devaluation in a saline-paired context but was impaired in the METH-paired context, a deficit that was also found when negative feedback was provided. Reductions in c-Fos-related immunoreactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 49 publications
5
49
0
Order By: Relevance
“…The current findings are consistent with past studies showing similar impairments in sensitivity to devaluation in contexts paired with ethanol (Ostlund et al, 2010) and methamphetamine (Furlong et al, 2015). While rats ate more JF than chow, and thus may have associated eating freely available food with the JF context which may, in some way, have interfered with having to earn food, as noted above, rats continued to respond in the JF context, they just did so indiscriminately.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current findings are consistent with past studies showing similar impairments in sensitivity to devaluation in contexts paired with ethanol (Ostlund et al, 2010) and methamphetamine (Furlong et al, 2015). While rats ate more JF than chow, and thus may have associated eating freely available food with the JF context which may, in some way, have interfered with having to earn food, as noted above, rats continued to respond in the JF context, they just did so indiscriminately.…”
Section: Discussionsupporting
confidence: 93%
“…Devaluation tests revealed that responding was insensitive to devaluation when rats were tested in the alcohol-paired context but goal-directed in the saline context (Ostlund et al, 2010). The second study used a similar procedure to demonstrate habitual control over behavior produced by contexts paired with methamphetamine (Furlong et al, 2015). Importantly, instrumental performance was reinforced with food rather than drug rewards and the animals were drug-free at test, indicating that the contexts, rather than acute intoxication, influenced the decision-making processes that promoted habitual responding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…goal-directed/action – object responding) to model-free (i.e. habitual/stimulus – response responding) learning following repeated exposure to reinforcers including drugs and food [5153] is a hallmark of addictive behavior [54] and observed in diet induced obesity [7]. …”
Section: Dopamine-dependent Functions Influencing Ingestive Behaviormentioning
confidence: 99%
“…By these functional interactions, striatopallidal A 2A Rs can modulate dopamine and glutamate signaling and striatal synaptic plasticity and cognitions including instrumental behaviors (Chen, 2014). Indeed, genetic inactivation of striatal A 2A Rs impaired habit formation (Yu et al, 2009) and pharmacological reduction of A 2A R-mediated cAMP-pCREB signaling in the dorsal medium striatum (DMS) enhanced goal-directed ethanol drinking (Nam et al, 2013) and reversed meth-amphetamine-induced facilitation of habit formation (Furlong et al, 2015). However, the mechanism underlying the A 2A R modulation of instrumental behaviors is not known.…”
Section: Introductionmentioning
confidence: 99%